Mažosios Lietuvos rankraštinės ir spausdintos knygos paveldas Lietuvos knygos muziejuje: projekto bandymas - Kaunas, Domas (Knygotyra, 2003)
The book museum models and reveals a complex and different world, in which intellectual expression and material culture interact in many ways. This world can be imitated by various typical and significant examples and images of literacy and press heritage. The literary and book culture of Lithuania Minor is very determined by space and time. Its territory is geographically defined by main landmarks: the coast of the Baltic Sea, the historical border between the Great Duchy of Lithuania and Prussia, along which Lithuanian place-names, hydronyms and the centres of ethnicity are collected. Essentially this is the West of the Republic of Lithuania (previously – Klaipėda region) and the region of Kaliningrad that at present belongs to Russian Federation.Time boundaries look as follows: the beginning of the sixteenth century – 1945. The recognition of the literacy and press heritage of Lithuania Minor meets the interests of modern ethnopolitic, research, and cultural interests of Lithuania. The territory of Lithuania Minor is also a field of interests of Germany and Poland, therefore the necessity to respect them and to form the relevant concept of museum exposition is vital. The most complicated tasks for the exposition would be the following: 1) to represent the heritage of Lithuanian literacy and press over 450 years in a comprehensive but laconic manner; 2) to identify the most valuable heritage; 3) to exhibit the most valuable heritage; 4) to aggregate the original exhibits.The most important exhibit of the museum will be a manuscript and a publication (a printed list, a pamphlet, a book, or a periodical). Lithuanian book should dominate from the point of view of language. But it should not be the only one. The exposition should reflect the relations of Lithuanian book with Latin, German and books in other languages in the region. The old Lituanistic book in German was sometimes even more important than in Lithuanian. The inherited value of literacy and press over centuries is revealed in the subject and typological cross-section of the repertoire. It consists of 3500 non-periodical and 150 periodical publications in Lithuanian. The museum exposition will require careful selection of those. The discussions about the criteria of selection are going on, but the book science has defined the most important ones: 1) manuscripts created before introduction of printing in a region, 2) the first printed books, 3) the first books in different subject areas (religion, linguistics, fiction, practical), 4) books of historical significance, 5) a book symbolising a historical personality. The book of Lithuania Minor also should be represented from the point of view of book architecture and art. This book was under the influence of the Protestant culture, therefore, it was usually modest and moderate. The main elements of internal decoration were the portrait of church authorities, simple ornaments on the topic of crucifixion, didactic pictures illustrating moral literature. The external decorations consisted of leather binding, blind or gold indentations, and copper buckles. A major element of the exposition is the iconography of the authors, publishers, printers, and booksellers. Partly it is already researched and collected, but a search should be conducted to find the old items in Germany and other European countries. The functioning of Lithuanian book in society might be reflected through ownership signs, public and private library catalogues, written evidence of contemporaries.